Shear strengthening of damaged reinforced concrete beams with hybrid composite plates - Baghi, Hadi (2017)
This paper aims to evaluate experimentally the potentialities of Hybrid Composite Plates (HCPs) technique for the shear strengthening and repairing of reinforced concrete (RC) beams. HCP is a thin plate of Strain Hardening Cementitious Composite (SHCC) reinforced with Carbon Fiber Reinforced Polymer (CFRP) laminates. For this purpose, an experimental program composed of four Rectangular and five T-cross section beams was executed to assess the strengthening efficiency of HCPs technique. There were two control beams without any type of shear reinforcement, and seven beams strengthened with HCPs. The HCPs were applied to the lateral faces of the beams by using a combination of epoxy adhesive and mechanical anchors. The bolts were applied with a certain torque in order to increase the concrete confinement. To have a better understanding of the shear behavior of SHCC material, Iosipescu shear tests were carried out, and the results were used to derive their fracture mode II parameters. To further explore the potentialities of the HCPs technique for the shear strengthening, the experimental tests were simulated numerically by a FEM-based computer program considering the material properties obtained experimentally. After demonstration of the good predictive performance of the numerical model, a parametric study was executed to investigate the influence of some parameters on the load carrying capacity of the strengthened beams, namely: i) Use a mortar instead of the SHCC; ii) application of different applied torque level to the mechanical anchors; iii) different bond condition between HCPs and concrete substrate.